TINJAUAN INSENTIF PPh BAGI SDM DI BIDANG KESEHATAN DALAM MASA PANDEMI VIRUS COVID-19 - Irawan Purwo Aji (Behavioral Accounting Journal, 2020)
In the time of the Covid-19 virus pandemic, human health resources are essential to treating patients or communities affected by the virus. In a form of appreciation for their work, Governments provide income tax incentives on income received by human resources or taxpayers working in the field of health, especially those dealing with patients or communities affected by the Covid-19 virus. There are some forms or schemes of tax incentives that are taxpayers receive. This research goal wants to study and explore what forms of incentives taxpayers receive. The study will provide a simulation of incentives that taxpayers will receive. Thus, taxpayers that treat patients or communities affected by the Covid-19 virus can understand the application and accounting of income tax incentives it receives.